Interior view of RIECo incinerator machinery - Ward, Phil, photographer ([between 1934 and 1950], 1934)
The image is typical of the stoking floor of most RIECo Incinerators in the 1930s.
Title from acquisition documentation.
Part of the collection: Eric Milton Nicholls collection.
Inscriptions: "Phil Ward, Commercial Photographer, 296 Pitt St. Sydney MA.1493"--Stamped on verso; "no copied"--In pencil lower right on verso.
Condition: Good.
Also available online
Purchased from Marie and Glynn Nicholls, 2006.
Keywords: Machinery -- Photographs; Incinerators -- Photographs